Estudo do papel do S-Nitrosoglutationa na doença periodontal experimental e na inflamação aguda - Menezes, Adriana Magalhães Andrade de (2010)
Periodontitis, a relevant cause of teeth loss in adults, is a chronic inflammatory disease characterized by alveolar bone resorption and collagen fibers and cementum destruction. S-nitrosogluthathione (GSNO) is considered to be an NO donor and to act as a reservoir of NO in vivo. The objective of this study was to investigate the effect of GSNO in experimental periodontal disease (EPD). EPD was induced by a nylon thread ligature surgically placed around the cervix of the second left maxillary molars of female Wistar rats. Animals were treated with 50μL GSNO (0,5, 2 or 10 mmol L-1), PVP or saline subgingivally 30 minutes before periodontits induction and daily until sacrifice on 11th day. The parameters analysed were alveolar bone loss (ABL), bone alkaline phosphatase, myeloperoxidase (MPO), cytokines levels (IL-1β and TNF-α), malondialdeyhyde (MDA), reduced glutathione (GSH) content, nitrite/nitrate levels, and immunohistochemistry for metalloproteinase (MMP-1/8), inducible nitric oxide syntase (iNOS) and nuclear factor-κB (NFκB). In order to confirm the anti-inflammatory and antioxidant effect of GSNO was used the peritonitis and paw edema models. Peritonitis was induced by injection of 1 mL carrageenan (500 μL/cavity) or saline ip in naïve rats or in rats that received saline, PVP or GSNO (0,5, 2 or 10 mmol L-1, ip) 1 hour prior to the carrageenan. After 4 hours, the animals were sacrificed for collection of the fluid peritoneal. Paw edema was induced by subplantar injection of carrageenan (500 g/paw). Saline, PVP or GSNO (0,5, 2 or 10 mmol L-1, ip) were administered 1 hour before the inflammatory stimuli into the left hind paw. The animals were sacrificed 4 hours after the ip injection of carrageenan. The parameters analysed were volume of paw edema, migration of leukocytes for cavity peritoneal, MPO, cytokines (IL-1β and TNF-α), GSH and MDA. The GSNO in the concentrations of 0,5 and 2 mmol L-1 reduced ABL, MPO, inflammatory cytokines (IL-1β and TNF –α), nitrite/nitrate, and it increased GSH. GSNO 0,5 and 2 mmol L-1 also decreased the demarcation to MMP-1/-8, NOSi and NF -κB. However, just GSNO 2 mmol L-1 reduced MDA. Results similar were found in the peritonitis and in the paw edema, added to the fact that GSNO 0,5 and 2 mmol L-1 decreased the volume of the paw edema and the migration of leukocytes and neutrophils to the cavity peritoneal. These results show that GSNO has a protective effect on the experimental periodontal disease, peritonitis and paw edema by reducing inflammation and oxidative stress.